2021
DOI: 10.1021/acs.inorgchem.1c00973
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Steric Hindrance via Ligand Design in Dysprosium Complexes: From Induced Slow Relaxation to Zero-Field Single-Molecule Magnet Properties

Abstract: The synthesis and magnetic characterization of three novel Dy compounds, [Dy{PPh 2 S((2), and [Dy{MeS(N t Bu) 3 } 2 (μ-Cl 2 )Li(THF) 2 ] (3), based on the sulfur−nitrogen ligands RS(N t Bu) x − (where R = PPh 2 , x = 2 for (1); R = Ph, x = 2 for (2); and R = Me, x = 3 for (3)) are reported. They represent rare examples of lanthanide-based complexes containing sulfur−nitrogen ligands, whose suitability to enhance the magnetic anisotropy in 3d metals was only recently established. Changes in the ligand field env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Lanthanide complexes are easily accessible through metathesis reactions and for that purpose, lithium precursors are convenient to use. However, our recent work showed that the successful optimization of the magnetic properties is limited by LiHal co‐complexation [13–15,17] …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lanthanide complexes are easily accessible through metathesis reactions and for that purpose, lithium precursors are convenient to use. However, our recent work showed that the successful optimization of the magnetic properties is limited by LiHal co‐complexation [13–15,17] …”
Section: Introductionmentioning
confidence: 99%
“…The SN ligands,[ 24 , 25 ] however, have recently shown their potential for SMM design for the following reasons (Scheme 1 ):[ 12 , 13 , 14 , 15 , 16 , 17 , 18 ] First, acute bite angles of the SN motif provide access to interesting and promising geometries. [ 12 , 14 ] Further, tuning the SN ligands served as model systems to find the ideal bite angles for tetrahedral Co II SMMs and allowed an increase of linearity in f‐metal SMMs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations